Hemokinin-1 induces transcriptomic alterations in pain-related signaling processes in rat primary sensory neurons independent of NK1 tachykinin receptor activation - Takács-Lovász, Krisztina; Aczél, Timea; Borbély, Éva; Szőke, Éva; Czuni, Lilla; Urbán, Péter; Gyenesei, Attila; Helyes, Zsuzsanna; Kun, József; Bölcskei, Kata (Frontiers in Molecular Neuroscience, 2023)
The tachykinin hemokinin-1 (HK-1) is involved in immunological processes, inflammation, and pain. Although the neurokinin 1 receptor (NK1R) is described as its main target, several effects are mediated by currently unidentified receptor(s). The role of HK-1 in pain is controversial, depending on the involvement of peripheral and central sensitization mechanisms in different models. We earlier showed the ability of HK-1 to activate the trigeminovascular system, but the mechanisms need to be clarified. Therefore, in this study, we investigated HK-1-induced transcriptomic alterations in cultured rat trigeminal ganglion (TRG) primary sensory neurons. HK-1 was applied for 6 or 24 h in 1 μM causing calcium-influx in these neurons, 500 nM not inducing calcium-entry was used for comparison. Next-generation sequencing was performed on the isolated RNA, and transcriptomic changes were analyzed to identify differentially expressed (DE) genes. Functional analysis was performed for gene annotation using the Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), and Reactome databases. NK1R and Neurokinin receptor 2 (NK2R) were not detected. Neurokinin receptor 3 (NK3R) was around the detection limit, which suggests the involvement of other NKR isoforms or other receptors in HK-1-induced sensory neuronal activation. We found protease-activated receptor 1 (PAR1) and epidermal growth factor receptor (EGFR) as DE genes in calcium signaling. The transmembrane protein anthrax toxin receptor 2 (ANTXR2), a potential novel pain-related target, was upregulated. Acid-sensing ion channel 1; 3 (Asic1,3), N-methyl-D-aspartate (NMDA) and alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) glutamate receptors decreased, myelin production and maintenance related genes (Mbp, Pmp2, Myef2, Mpz) and GNDF changed by HK-1 treatment. Our data showed time and dose-dependent effects of HK-1 in TRG cell culture. Result showed calcium signaling as altered event, however, we did not detect any of NK receptors. Presumably, the activation of TRG neurons is independent of NK receptors. ANTXR2 is a potential new target, PAR-1 has also important role in pain, however their connection to HK-1 is unknown. These findings might highlight new targets or key mediators to solve how HK-1 acts on TRG.